Mental health of individuals with pre-existing mental illnesses at the beginning of the COVID-19 pandemic: results of the German National Cohort (NAKO) - Stein, Janine; Pabst, Alexander; Berger, Klaus; Karch, André; Teismann, Henning; Streit, Fabian; Grabe, Hans J.; Mikolajczyk, Rafael; Massag, Janka; Lieb, Wolfgang; Castell, Stefanie; Heise, Jana-Kristin; et al. (Frontiers in Public Health, 2024)
Background: The COVID-19 pandemic prompted a range of studies on mental health, with mixed results. While numerous studies reported worsened conditions in individuals with pre-existing mental disorders, others showed resilience and stability in mental health. However, longitudinal data focusing on the German population are sparse, especially regarding effects of age and pre-existing mental disorders during the early stages of the pandemic. Objectives: To assess the interplay between psychiatric history, age, and the timing of the pandemic, with a focus on understanding how these factors relate to the severity of depression and anxiety symptoms. Methods: Exploratory analyses were based on 135,445 individuals aged 20-72 years from the German National Cohort (NAKO). Depressive and anxiety symptoms were assessed before and after the first wave of the pandemic. Inferential statistical analyses and negative binomial regression models were calculated. Results: Persons with a self-reported psychiatric history exhibited comparable levels of depression and anxiety symptom severity after the first wave of the pandemic compared to the time before. In contrast, individuals without a psychiatric history, particularly those in their 20s to 40s, experienced an increase in mental health symptom severity during the first wave of the pandemic. Limitations: Analyses focuses on the first wave of the pandemic, leaving the long-term mental health effects unexplored. Conclusion: Future research should consider age-specific and mental-health-related factors when addressing global health crises. Additionally, it is important to explore factors influencing resilience and adaptation, aiming to develop targeted interventions and informed policies for effective mental health management during pandemics.
Gesehen am 23.10.2024